Prospects, opportunities and challenges of the transition to 12-year education system in Kazakhstan - Tykezhanova, G.M.; Yelshina, B.B.; Estemesova, K.A. (Fundamental and Experimental Biology, 2016)
The article deals with the transition to 12-year education which is a justified step. Since the negative factors affecting the development of the national pre-school models — old system of evaluation of educational achievements are not able to stimulate students led the transition of the education system of Kazakhstan to world standards. In turn, the 12-year-old system of education makes it possible to take into account more fully the interests, needs and capabilities ofparticipants in the educational process and to more efficiently reallocate training material on curricula.